2011
DOI: 10.1093/jscr/2011.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Periampullary carcinoma in a patient with agenesis of dorsal pancreas

Abstract: Agenesis of dorsal pancreas is a rare developmental anomaly. We here report a case of agenesis of dorsal pancreas in a patient of periampullary carcinoma and highlight its implications on the management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The pathological result showed that our ADP case was associated with chronic suppurative pancreatitis, with moderate hyperplasia in focal ductal epithelium of the pancreas, which was actually considered to be the precancerous lesion of the pancreas. Previous studies have confirmed that ADP patients may combine with chronic pancreatitis and periampullary tumors including pancreatic adenocarcinoma, neuroendocrine tumor, solid pseudopapillary tumor of the pancreas, and cholangiocarcinoma [18,28–31] . Cholangiocarcinoma and solid pseudopapillary tumor of the pancreas were described to be combined with Chinese ADP patients in our review as well [8,10]…”
Section: Discussionsupporting
confidence: 74%
“…The pathological result showed that our ADP case was associated with chronic suppurative pancreatitis, with moderate hyperplasia in focal ductal epithelium of the pancreas, which was actually considered to be the precancerous lesion of the pancreas. Previous studies have confirmed that ADP patients may combine with chronic pancreatitis and periampullary tumors including pancreatic adenocarcinoma, neuroendocrine tumor, solid pseudopapillary tumor of the pancreas, and cholangiocarcinoma [18,28–31] . Cholangiocarcinoma and solid pseudopapillary tumor of the pancreas were described to be combined with Chinese ADP patients in our review as well [8,10]…”
Section: Discussionsupporting
confidence: 74%
“…The mechanism of tumorigenesis in ADP patients is unclear, but chronic pancreatitis caused by the ADP itself could be one of the risk factors for neoplasia [2]. Thus, the association of tumorigenesis with ADP indicates that every ADP patient should be observed with a focus on the early detection of pancreatic neoplasia [4,5,22,23]. According to literature reports and our own study, the clinical features of SPTs in patients with ADP are similar to those observed in patients without ADP [12,13,21,24,25].…”
Section: Discussionsupporting
confidence: 53%
“…Solid pseudopapillary tumor in patients with agenesis of the dorsal pancreas reported in the world SPT of the pancreas with ADP is extremely rare, with only two cases having been reported in the literature prior to this study, 21 Herein, we describe another three cases, making a total of five reported thus far. More than 10 ADP cases have been associated with pancreatic neoplasia, although only about 100 occurrences of ADP are recorded in the literature, [1][2][3][4][5][6] The mechanism of tumorigenesis in ADP patients is unclear, but chronic pancreatitis caused by the ADP itself could be one of the risk factors for neoplasia, 2 Thus, the association of tumorigenesis with ADP indicates that every ADP patient should be observed with a focus on the early detection of pancreatic neoplasia, 4,5,22,23 According to literature reports and our own study, the clinical features of SPTs in patients with ADP are similar to those observed in patients without ADP, 12,13,21,24,25 This tumor usually occurs in young females, with less than 10% of cases reported in males. 11,26 Our series also agrees with previous research in terms of the most common localization of SPTs 27 and the most frequent symptom 10,12,14,21,25 being the pancreas head and epigastric pain, respectively.…”
Section: Discussionmentioning
confidence: 99%